Discovering the values of the Islamic garden - Md Jani, Haza Hanurhaza; Harun, Nor Zalina; Mansor, Mazlina; Zen, Ismawi (e-International Publishing House, Ltd., UK., 2017)
This paper aims to investigate the values and the characteristics of the Islamic garden design. It reviews several dimensions of studies that are significant to understand the Islamic garden concept and its characteristics. The outcomes of this research assist in strengthening the understanding towards the importance of protecting and continuing the legacy of the Muslim civilisation.